Balancing tourism, conservation, and development: a political ecology of ecotourism on the Galapagos Islands. Issue 1 (2nd January 2016) - Mathis, Adrienne; Rose, Jeff
Abstract : Thousands of tourists venture to the internationally renowned Galapagos Islands each year to admire the same pristine nature Darwin came upon over 150 years ago. While appreciating the landscape, many visitors fail to understand the interconnectedness of the tourism industry, Galapagos conservation efforts, and development on the inhabited islands of the archipelago. This research stems from 6 weeks of in-depth field research on San Cristóbal Island, Galapagos Islands, and demonstrates the ways in which island residents are forced to navigate the complex intersection of tourism, conservation, and development on the most local scale. Conservation political ecology examines the asymmetrical power relations in protected areas. Therefore, to understand the impacts of conservation and tourism on local communities, political ecology frames research findings to illustrate how relationships between conservation, tourism, and development have altered not only the San Cristóbal community, but also locals' perceptions of various actors, their own agency, and Galapagos nature. The San Cristóbal municipal government aims to implement a version of 'true' ecotourism, which would allow residents to reclaim political agency, yet the lack of aid and transparency throughout larger scales of Ecuadorian governance challenges these local ideals.